2014
DOI: 10.1111/1471-0528.12629
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐eclampsia, eclampsia and adverse maternal and perinatal outcomes: a secondary analysis of the World Health Organization Multicountry Survey on Maternal and Newborn Health

Abstract: Objective To assess the incidence of hypertensive disorders of pregnancy and related severe complications, identify other associated factors and compare maternal and perinatal outcomes in women with and without these conditions.Design Secondary analysis of the World Health Organization Multicountry Survey on Maternal and Newborn Health (WHOMCS) database.Setting Cross-sectional study implemented at 357 health facilities conducting 1000 or more deliveries annually in 29 countries from Africa, Asia, Latin America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
360
11
21

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 451 publications
(415 citation statements)
references
References 38 publications
23
360
11
21
Order By: Relevance
“…The incidence of hypertensive disorders in pregnancy in our study (27.5 per 1000 deliveries) was similar to the finding of secondary analysis of the World Health Organization Multicounty Survey on Maternal and Newborn Health from 29 countries in Africa, Asia, Latin America and the Middle East (27.3 per 1000 deliveries) and showed various geographic distribution [6]. A previous study conducted in central of Thailand reported the prevalence of preeclampsia accounted for 47 per 1000 deliveries [7].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The incidence of hypertensive disorders in pregnancy in our study (27.5 per 1000 deliveries) was similar to the finding of secondary analysis of the World Health Organization Multicounty Survey on Maternal and Newborn Health from 29 countries in Africa, Asia, Latin America and the Middle East (27.3 per 1000 deliveries) and showed various geographic distribution [6]. A previous study conducted in central of Thailand reported the prevalence of preeclampsia accounted for 47 per 1000 deliveries [7].…”
Section: Discussionsupporting
confidence: 89%
“…A previous study conducted in central of Thailand reported the prevalence of preeclampsia accounted for 47 per 1000 deliveries [7]. The different reports on the incidence of hypertensive subgroups was mainly because the different classifications were chosen [5][6][7]. Maternal age at ≥35 years were consistently reported to be the concurrent risk of hypertensive disorders in pregnancy [5,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding hemorrhage and high blood pressure, studies have reported an increased risk of perinatal death 25,26 , prematurity, low birth weight, and asphyxia at birth 15 among infants of mothers with hypertension in pregnancy, still a common condition during pregnancy 27,28 , and of mothers with vaginal hemorrhage prior to labor 17,29 .…”
Section: Discussionmentioning
confidence: 99%
“…WHO multi country survey reveals incidence of gestational hypertension (4.4%), preeclampsia (3%), eclampsia (0.8%) and chronic hypertension (0.1%) in India. 1 While hospital incidence of hypertensive disease of pregnancy is 7.8% in Bharati Hospital and Research Centre.…”
Section: Introductionmentioning
confidence: 99%